Development of Cimandaway Waterfall Natural Tourism Potential in Serang Village, Datar Village, Cilacap Central Java - Hayatunnisa, Sintia; Ibnu, Apep; Dewi, Hestiana; Eka, Ibnu; Bayu Brahmantia (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
A tourist attraction will be able to increase people's income, create new jobs and increase regional income if the tourist attraction is crowded with tourists. To attract tourists, of course, must meet certain conditions so that tourism meets these requirements, then a tour needs to be developed and planned properly. The Curug Cimandaway tourist attraction in Datar Village, Cilacap Regency is not re-managed so we are interested in researching and developing the Curug, the informants of this research are the Village Head, Hamlet Head, RT and RW in Serang Hamlet, Datar Village. The purpose and benefits of the research to be obtained are to identify and find out the potential and problems faced in the development of objects and tourist attractions of Curug Cimandaway. The method used is in-depth interviews with informants. The main data collection tool is the researcher himself using interview instruments and observation documentation to determine the strategy for developing Curug Cimandaway tourism object